Progress towards control of the acute respiratory viral diseases of childhood - Pringle, C. R. (1987)
Many of the common respiratory illnesses of infancy and childhood are caused by viruses of the Paramyxoviridae family, in particular measles virus, respiratory syncytial (RS) virus and parainfluenzavirus type 3 (PI3). Effective measles vaccine was developed by classical methods, but these same methods have failed to provide vaccines to control RS and PI3 virus infections. The WHO Programme for Vaccine Development was initiated in 1983 to encourage the application of the new biotechnologies to continuing problems, such as the acute virus-induced respiratory diseases of childhood. At a meeting of research workers held in July 1986 under the auspices of this programme, renewed optimism was expressed concerning the prospects for immunoprophylaxis of RS virus-induced disease. Animal models are now available for evaluation of the immunogenic potential of candidate vaccines. Vaccinia/RS recombinant viruses have been produced which have allowed the immunogenic properties of individual RS virus proteins to be defined. Complete protection without the exacerbation of disease, which earlier had accompanied the use of formalin-inactivated vaccines, has been achieved in animals immunized with vaccinia virus recombinants expressing the F protein; partial protection was obtained using G protein gene vectors. PI3 appears to be an inherently stable virus and evidence from animal experiments suggests that bovine PI3 might be suitable for use as a live vaccine in man.